Women in Ancient China - Hinsch, Bret (An Asia/Pacific/perspectives series, 2018)
This pioneering book provides a comprehensive survey of ancient Chinese women's history, covering thousands of years from the Neolithic era to China's unification in 221 BCE. For each period-Neolithic, Shang, Western Zhou, and Eastern Zhou-Hinsch explores central aspects of female life such as marriage, family life, politics, ritual, and religious roles.